EVALUATION OF DEEP LEARNING IMPLEMENTATION IN STRENGTHENING ELEMENTARY STUDENTS’ CHARACTER EDUCATION IN THE ERA OF ARTIFICIAL INTELLIGENCE AND THE MERDEKA CURRICULUM - Enjoni Enjoni; Arlina Yuza; Agus Waldi; Fazri Zuzano (Study program PGSD FKIP Universitas Bung Hatta, 2026)
This study aims to critically explore the urgency of evaluating the implementation of Deep Learning in strengthening character education for elementary school students in the era of Artificial Intelligence and the Merdeka Curriculum in Indonesia. Using a qualitative approach through literature review analysis, this research examines various international and national scholarly sources related to the concepts of Deep Learning, character education, AI integration in learning, and the implementation of the Merdeka Curriculum in primary education. Data were analyzed using content analysis and critical synthesis techniques to identify conceptual patterns, contributions, and implementation challenges. The findings reveal that Deep Learning has significant potential to strengthen character education through meaningful, reflective, collaborative, and contextual learning aligned with the Pancasila Student Profile framework. The integration of Artificial Intelligence further enhances learning effectiveness through personalization and data-driven analytics; however, its implementation is still constrained by gaps in teachers’ digital literacy, infrastructure limitations, and ethical concerns regarding technology use. This study concludes that the implementation of Deep Learning in elementary schools is still in a transitional phase from conceptual understanding to practical application.